2015
DOI: 10.1016/j.atherosclerosis.2015.07.029
|View full text |Cite
|
Sign up to set email alerts
|

Utility of a genetic risk score to predict recurrent cardiovascular events 1 year after an acute coronary syndrome: A pooled analysis of the RISCA, PRAXY, and TRIUMPH cohorts

Abstract: Background Limited evidence exists regarding the utility of genetic risk scores (GRS) in predicting recurrent cardiovascular events after acute coronary syndrome (ACS). We sought to determine whether a GRS would predict early recurrent cardiovascular events within 1 year of ACS. Methods & Results Participants admitted with acute coronary syndromes from the RISCA, PRAXY, and TRIUMPH cohorts, were genotyped for 30 single nucleotide polymorphisms (SNPs) associated with coronary artery disease (CAD) or myocardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 39 publications
2
21
0
Order By: Relevance
“…The SNPs included in all these 3 GRSs are either identical to ours or represent the same gene region but with a different proxy SNP with minor exceptions. Compared with the GRSs of Tragante et al 16 , Mega et al, 17 and Labos et al, 18 our GRS with 47 SNPs comprised considerably more risk variants and accordingly covered a greater proportion of the genetic predisposition to CAD. Labos et al 18 had a slightly different focus and thus a shorter follow-up than our study, which potentially explains why the association between the GRS and the recurrent ACS could not be shown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The SNPs included in all these 3 GRSs are either identical to ours or represent the same gene region but with a different proxy SNP with minor exceptions. Compared with the GRSs of Tragante et al 16 , Mega et al, 17 and Labos et al, 18 our GRS with 47 SNPs comprised considerably more risk variants and accordingly covered a greater proportion of the genetic predisposition to CAD. Labos et al 18 had a slightly different focus and thus a shorter follow-up than our study, which potentially explains why the association between the GRS and the recurrent ACS could not be shown.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the GRSs of Tragante et al 16 , Mega et al, 17 and Labos et al, 18 our GRS with 47 SNPs comprised considerably more risk variants and accordingly covered a greater proportion of the genetic predisposition to CAD. Labos et al 18 had a slightly different focus and thus a shorter follow-up than our study, which potentially explains why the association between the GRS and the recurrent ACS could not be shown. The rather limited number of recurrent events in the study by Tragante et al 16 might account for the relatively weak association found in that study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several such scores have been developed based largely on alleles associated with risk of coronary disease or myocardial infarction from genome-wide association studies (GWAS), and have shown modest improvements in predicting coronary events independent of family history or cardiovascular risk factors in some studies [39,40] but not in others [41,42]. Still, such scores have been used to identify individuals at intermediate risk, where scores tend to have their greatest impact on reclassification, and to compare the effectiveness of risk reduction strategies in patients (and their clinicians) who were provided genetic risk information vs. those in whom it was withheld [43,44].…”
Section: Opportunities For Genomic Medicine Implementation Relatedmentioning
confidence: 99%
“…23 On the other hand, a panel of 30 single nucleotide polymorphisms associated with an increased risk of MI, aggregated into a genetic risk score, failed to predict recurrent CV events within 1 year in 3 cohorts. 24 …”
Section: Other Potentially Useful Biomarkers In Acsmentioning
confidence: 99%